2018
DOI: 10.1016/j.desal.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Review on strategies for biofouling mitigation in spiral wound membrane systems

Abstract: Review on strategies for biofouling mitigation in spiral wound membrane systems. Desalination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 96 publications
0
41
0
1
Order By: Relevance
“…Similarly, Ashhab et al [274] reported that the secreted microbial substances not only influence film formation but also increase the viscosity of the mixed liquor. Consequently, this effect resulted in a significant increase in the overall hydraulic drag force [275,276]. However, measures and techniques to avert biofouling in MBR have been investigated under different conditions by several researchers.…”
Section: Microbial Foulants As Related To Pome Treatmentmentioning
confidence: 99%
“…Similarly, Ashhab et al [274] reported that the secreted microbial substances not only influence film formation but also increase the viscosity of the mixed liquor. Consequently, this effect resulted in a significant increase in the overall hydraulic drag force [275,276]. However, measures and techniques to avert biofouling in MBR have been investigated under different conditions by several researchers.…”
Section: Microbial Foulants As Related To Pome Treatmentmentioning
confidence: 99%
“…Membranes are affected by four main types of foulants, namely: (a) inorganic/crystalline, (b) organic, colloidal, (c) microbiological or biofouling and (d) particulate [68][69][70]. Among these, biofouling is the major problem because it reduces the efficiency of the system and also contributes to high economic and environmental costs of operating by attachment and proliferation of microorganisms on the surface of membrane [71][72][73]. Therefore, many efforts have been implemented to prevent fouling problems, namely pre-treatment, cleaning-in-place, and membrane modifications [74,75].…”
Section: Membrane and Membrane Processesmentioning
confidence: 99%
“…The microbial biofilm is developed by dynamic processes: (i) reversible attachment by attractive interactions between membrane surface and bacteria, (ii) irreversible attachment by specific or non-specific bacterial adhesions, (iii) micro-colony formation, (iv) biofilm maturation, and (v) dispersion [22]. It is claimed that even if 99.9% of all bacteria are eliminated by pretreatment, some bacteria will still enter the membrane system, adhering and multiplying utilizing biodegradable nutrients in the water passing the pretreatment [23,24].…”
Section: Lh Kim Et Al / Desalination and Water Treatment 126 (2018mentioning
confidence: 99%
“…Modified spacer geometries and surfaces may be a suitable solution to control biofouling [24]. The impact of spacer design on (i) biofilm development, (ii) membrane performance, and (iii) biofouling reduction can be studied using MFSs.…”
Section: Impact Of Feed Spacer Geometrymentioning
confidence: 99%
See 1 more Smart Citation